The genesis of the textile industry from adorned nudity to ritual regalia : the changing role of fibre crafts and their evolving techniques of manufacture in the ancient Near East from the Natufian to the Ghassulian - Levy, Janet, (Archaeopress Archaeology, 2020)
The Genesis of the Textile Industry from Adorned Nudity to Ritual Regalia documents and evaluates the changing role of fibre crafts and their evolving techniques of manufacture and also their ever-increasing wider application in the lives of the inhabitants of the earliest villages of the Ancient Near East. It is a broad-spectrum enquiry into fibre working in a broad swathe from Mesopotamia across Persia and Anatolia to the Nile Valley. It focuses, however, on the southern Levant from incipient sedentism in the Natufian culture, c. 13,000 cal BCE to the Ghassulian culture, c. 4500-3800/3700 cal BCE. This is the first comprehensive study addressing the fibre technologies of the southern Levant on a long chronological axis. Currently, fibre crafts play only a minor role in archaeological thinking.